PEMASANGAN PAPAN EDUKASI SAMPAH DI KAMPUNG NAENA MUKTIPURA - Antje Tuasela; Siske Tontong; Risma Amelia; Marta Febriyanti; Fitri Fitri; Anita Zilvana (JOURNAL OF COMMUNITY DEDICATION, 2026)
Waste remains an environmental issue facing the people of Naena Muktipura Village, Iwaka District, Mimika Regency. Lack of public awareness of the decomposition time of waste and the habit of littering are key issues identified based on field observations. In response to this situation, Group 1 of the Student Creativity Program (PKM) implemented an Environmental Care Movement by creating and installing waste education boards as a visual educational tool for the community. This activity aims to raise public awareness of the dangers of inorganic waste and the importance of maintaining a clean environment. The implementation method is carried out collaboratively within students, including needs analysis, preparation, implementation, and evaluation. The educational boards are designed to be simple and informative, featuring real-life examples of waste and information on the decomposition time. They are then installed in strategic locations for easy access and reading by the public. The results of the activity showed that the educational boards were installed effectively and received a positive response from the community. The boards attracted residents' attention and increased their understanding of the long-term impacts of waste. This activity is expected to foster collective community awareness of maintaining a clean environment sustainably.